A METHOD FOR FINITE ELEMENT MESH GENERATION FOR 2-D PROBLEMS - Muzaffer TOPCU (Pamukkale University Journal of Engineering Sciences, 1997)
The first step in numerical analysis techniques is the preparation of a suitable mesh for solution domain. In the finite element method, the mesh generation, as a preprosessing stage, affects the accuracy of the results importantly. Furthermore, it is very time consuming when it is not carried out automatically. In this study, an automatic mesh generation technique which can be used for plane and axisymmetric problems is introduced. Meshes prepared with this technique for several geometries are given. With the computer program developed for this study, the desired domains can be divided into 3 node triangular and 4, 8 and 9 node quadrilateral elements with least input information and suitably fine meshes.